2020
DOI: 10.22270/jddt.v10i1.3846
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Stability Indicating RP-HPLC Method for Estimation of Cilnidipine

Abstract: Cilnidipine is one of the dihydropyridine calcium antagonists. It was created combinedly by Fuji Viscera Pharmaceutical Company, Ajinomoto and Japan and was approved in the year 1995. Cilnidipine acts on N-type calcium channel where exist the end of sympathetic nerve in addition to common L-type calcium channel like that of other calcium antagonists. China, Japan, India, Korea and several other countries approved this drug. The objective of the method validation is to demonstrate whether the method was suited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…An extensive literature review reveals that different analytical methods like HPTLC [4,5], RP-HPLC [6][7][8][9][10][11][12], RP-UPLC [13], UV [14], and LC-MS [15,16] have been reported for the estimation of AZL. HPTLC [17][18][19], UV [20][21][22] and RP-HPLC [23][24][25][26][27][28] methods have been reported for analysis of CLN in the bulk and pharmaceutical dosage form.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive literature review reveals that different analytical methods like HPTLC [4,5], RP-HPLC [6][7][8][9][10][11][12], RP-UPLC [13], UV [14], and LC-MS [15,16] have been reported for the estimation of AZL. HPTLC [17][18][19], UV [20][21][22] and RP-HPLC [23][24][25][26][27][28] methods have been reported for analysis of CLN in the bulk and pharmaceutical dosage form.…”
Section: Introductionmentioning
confidence: 99%
“…Cilnidipine (CIL) is a calcium channel blocker used to treat heart conditions such as angina and excessive blood pressure [18]. According to the literature study, several stability-indicating RP-HPLC methods have been reported for the estimation of CIL alone and with other drugs [19][20][21][22][23][24][25]. Methanol and acetonitrile were used as mobile phase components and diluents for sample pretreatment in the reported chromatographic procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The third target CLN is a novel calcium channel blocker used to manage hypertension and chemically known as (±)-(E)-Cinnamyl 2-methoxyethyl-1,4-dihydro-2,6-dimethyl-4-(m-nitrophenyl)-3,5-pyridinedicarboxylate (Supporting Information Figure S1C) [20]. The literature survey revealed that HPLC [21][22][23][24][25][26], HPTLC [27][28][29], and LC-MS [30][31][32][33][34][35] procedures are reported to date for quantification of MET, TEL, and CLN individually and in combination with different drugs. However, no analytical methods are reported for MET, TEL, and CLN's simultaneous quantification in their newly fixed-dose combination.…”
Section: Introductionmentioning
confidence: 99%